A nose for lizards; can a detection dog locate the endangered pygmy bluetongue lizard (Tiliqua adelaidensis)?. Issue 2 (2nd July 2016) - Nielsen, Torben P.; Jackson, Gary; Bull, C. Michael
ABSTRACT: Environmental detection dogs have been used in various research and conservation projects. By detecting scent, dogs are capable of finding animals or scats that are virtually undetectable to humans. The endangered pygmy bluetongue lizard ( Tiliqua adelaidensis ) is endemic to heavily fragmented patches of native grassland in the mid-north region of South Australia. The lizards live in spider burrows with entrance diameters of 10–20 mm, which makes them difficult to find. This study presents the first data showing that a dog can detect pygmy bluetongue lizards. The dog showed the ability to distinguish between pygmy bluetongue lizard scent and the scent of sleepy lizard ( Tiliqua rugosa ) and bearded dragon ( Pogona barbata ). The dog also found more than 30 occupied lizard burrows in the field. Up until now surveys of this endangered lizard have relied on human visual detection of burrows, which is a very labour-intensive process. Although the climate and the ecology of the lizards pose a challenge to detection dogs, this study showed that their use in surveys of pygmy bluetongue lizards could potentially increase efficiency and accuracy, while lowering the cost and the workload.